1999
DOI: 10.1006/viro.1999.9920
|View full text |Cite
|
Sign up to set email alerts
|

DNA Contacts by Protein Domains of the Molluscum Contagiosum Virus Type-1B Topoisomerase

Abstract: All poxviruses studied encode a type 1B topoisomerase that introduces transient nicks into DNA and thereby relaxes DNA supercoils. Here we present a study of the protein domains of the topoisomerase of the poxvirus molluscum contagiosum (MCV), which allows us to specify DNA contacts made by different domains. Partial proteolysis of the enzyme revealed two stable domains separated by a protease-sensitive linker. A fragment encoding the linker and carboxyl-terminal domain (residues 82-323) was overexpressed in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Four conserved amino acid side chains found in all type IB topoisomerases (Arg-130, Lys-167, Arg-223, and His-265 in the vaccinia enzyme) are responsible for catalyzing the attack by tyrosine on the scissile phosphodiester to form the covalent intermediate (10 -12). The topoisomerase binds to DNA as a C-shaped protein clamp formed by an 80-amino acid N-terminal domain that contacts the DNA major groove and a 234-amino acid C-terminal catalytic domain that interacts with the scissile phosphate on the minor groove face of the double helix (13)(14)(15)(16)(17)(18). The crystal structure of vaccinia topoisomerase in the free state (16) showed that several of the catalytic residues are either disordered (Arg-130) or out of position to perform transesterification chemistry (Lys-167, Tyr-274), implying that the active site is not pre-assembled.…”
mentioning
confidence: 99%
“…Four conserved amino acid side chains found in all type IB topoisomerases (Arg-130, Lys-167, Arg-223, and His-265 in the vaccinia enzyme) are responsible for catalyzing the attack by tyrosine on the scissile phosphodiester to form the covalent intermediate (10 -12). The topoisomerase binds to DNA as a C-shaped protein clamp formed by an 80-amino acid N-terminal domain that contacts the DNA major groove and a 234-amino acid C-terminal catalytic domain that interacts with the scissile phosphate on the minor groove face of the double helix (13)(14)(15)(16)(17)(18). The crystal structure of vaccinia topoisomerase in the free state (16) showed that several of the catalytic residues are either disordered (Arg-130) or out of position to perform transesterification chemistry (Lys-167, Tyr-274), implying that the active site is not pre-assembled.…”
mentioning
confidence: 99%
“…19). This, in turn, appears to cause the free 5Ј-sulfhydryl (which replaces the 5Ј-hydroxyl in this trapped covalent complex; 8,19,[23][24][25][26][27][28] in the nicked DNA strand to shift away from the covalent phosphotyrosine linkage and form a hydrogen bond with the side chain of Asn-722, an interaction not observed in previous topoisomerase I covalent complexes (Figs. 4A and 6).…”
Section: Discussionmentioning
confidence: 75%
“…The G base in italics contained a bridging phosphorothiolate linkage, which upon cleavage by human topoisomerase I generates a free 5Ј-sulfhydryl rather than a hydroxyl (22)(23)(24)(25)(26)(27)(28). This method of trapping human topoisomerase I in covalent complexes with duplex DNA has been used previously in structural studies of this enzyme (8,19), as well as in several detailed mechanistic and biological studies of topoisomerases and related tyrosine recombinases (22)(23)(24)(25)(26)(27)(28). Note that the Ara-C nucleotide is in the intact DNA strand, and the G nucleotide containing the 5Ј-bridging phosphorothiolate linkage is in the scissile DNA strand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The poxvirus topoisomerases are two-domain proteins (22)(23)(24)(25) that bind to the 5Ј-(T/C)CCTT-3Ј site as monomers by forming C-shaped clamps around the DNA (22,23,26). Comparison of the vaccinia amino and carboxyl domain structures determined in the absence of DNA (23,25) to the smallpox-topoisomerase/DNA complex (22) allowed the conformational changes that mediate activation to be visualized.…”
mentioning
confidence: 99%